Perancangan Video Profile Museum Sekolah SMP Negeri 1 Ungaran - Agnes Naomi; Anthony Y.M. Tumimomor (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The SMPN 1 Ungaran school museum is the only school museum found in semarang district. The museum is located in the SMPN 1 Ungaran complex that during the Dutch Indies was used as kweekschool. The Museum Buildings have a high historical value for civilization in the city of Ungaran and are now being used as a school museum that houses the most impressive collections that have ever occurred in this school and are not found in any other. There are many people who are unaware of the existence of the school's museum, but at the same time the museum has difficulty trying to explain the history, profile and detail of the museum collection when, having or attending educational exhibitions or similar events. Looking at the problem, it would require an audio-visual solution packed into a profile video capable of providing information about the school's museum profile. Applying qualitative methods and linear strategies, it is hoped to produce a video profile that can provide information on the history of museum buildings, museum profiles and museum collections in greater detail and interest to the general public, making its existence known.